Secular changes of height and body mass of children and youth in the Bydgoszcz region - Nowicki, Grzegorz (Polskie Towarzystwo Antropologiczne, 2000)
The secular changes of height and body mass of girls and boys in the Bydgoszcz region in the period between 1935 and 1991 have been presented in this paper. Over the period of 56 years changes of the traits under invastigation showed periodical diversification. Between 1935-1946 a regress was observed, between 1952 and 1971 the greatest average secular changes took place, the years from 1972 to 1979 were characterized by a slowdown in the changes, and in the period from 1979 through 1991 there was a set back in the secular trend of the investigated traits. This is probably due to the fluctuation of the secular changes occures in age groups 13.5 years, 14.5 years, and 15.5 years. Analysis of the research results indicates that the changes are more conspicuous among boys than among girls.
Keywords: Secular changes; Physical development; Children of Bydgoszcz region